Detection and strain typing of ancient Mycobacterium leprae from a medieval leprosy hospital. - G Michael Taylor (PLoS ONE, 2013)
Nine burials excavated from the Magdalen Hill Archaeological Research Project (MHARP) in Winchester, UK, showing skeletal signs of lepromatous leprosy (LL) have been studied using a multidisciplinary approach including osteological, geochemical and biomolecular techniques. DNA from Mycobacterium leprae was amplified from all nine skeletons but not from control skeletons devoid of indicative pathology. In several specimens we corroborated the identification of M. leprae with detection of mycolic acids specific to the cell wall of M. leprae and persistent in the skeletal samples. In five cases, the preservation of the material allowed detailed genotyping using single-nucleotide polymorphism (SNP) and multiple locus variable number tandem repeat analysis (MLVA). Three of the five cases proved to be infected with SNP type 3I-1, ancestral to contemporary M. leprae isolates found in southern states of America and likely carried by European migrants. From the remaining two burials we identified, for the first time in the British Isles, the occurrence of SNP type 2F. Stable isotope analysis conducted on tooth enamel taken from two of the type 3I-1 and one of the type 2F remains revealed that all three individuals had probably spent their formative years in the Winchester area. Previously, type 2F has been implicated as the precursor strain that migrated from the Middle East to India and South-East Asia, subsequently evolving to type 1 strains. Thus we show that type 2F had also spread westwards to Britain by the early medieval period.